2012
DOI: 10.1021/bi300249u
|View full text |Cite
|
Sign up to set email alerts
|

MacA is a Second Cytochrome c Peroxidase of Geobacter sulfurreducens

Abstract: The metal-reducing δ-proteobacterium Geobacter sulf urreducens produces a large number of c-type cytochromes, many of which have been implicated in the transfer of electrons to insoluble metal oxides. Among these, the dihemic MacA was assigned a central role. Here we have produced G. sulf urreducens MacA by recombinant expression in Escherichia coli and have solved its three-dimensional structure in three different oxidation states. Sequence comparisons group MacA into the family of diheme cytochrome c peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 43 publications
1
50
0
Order By: Relevance
“…However, genetic studies showed that the phenotype of the ccpA mutant strain of G. sulfurreducens was similar to that of the wild-type during growth on all tested electron acceptors (Table 5). macA (GSU0466), encoding a second peroxidase that is very similar to CcpA and capable of electron transfer to PpcA, a c-type cytochrome that is important for growth on Fe(III) citrate (Seidel et al, 2012), is upregulated only on Mn(IV) oxides (Table 4); however, a knockout of macA resulted in impaired growth on soluble and insoluble Fe(III) but not on Mn(IV) oxide (Table 5 and Fig. 1).…”
Section: Additional Electron Transport Genes Upregulated During Growtmentioning
confidence: 99%
“…However, genetic studies showed that the phenotype of the ccpA mutant strain of G. sulfurreducens was similar to that of the wild-type during growth on all tested electron acceptors (Table 5). macA (GSU0466), encoding a second peroxidase that is very similar to CcpA and capable of electron transfer to PpcA, a c-type cytochrome that is important for growth on Fe(III) citrate (Seidel et al, 2012), is upregulated only on Mn(IV) oxides (Table 4); however, a knockout of macA resulted in impaired growth on soluble and insoluble Fe(III) but not on Mn(IV) oxide (Table 5 and Fig. 1).…”
Section: Additional Electron Transport Genes Upregulated During Growtmentioning
confidence: 99%
“…This model suggests that electrons are transferred from the menoquinone pool within the inner membrane to MacA which then transfers electrons PpcA [163], which shuttles the electrons across the periplasm to a Pcc complex [33]. The Pcc complex passes electrons to the OMCs OmcE and OmcS, which may be responsible for the transfer of electrons to pili [161,165] of which OmcS is attached [14,[166][167][168], however G. sulfurreducens can also transfer electrons directly using OMCs, without the involvement of pili [165].…”
Section: Abundance Of Eet Related Proteinsmentioning
confidence: 99%
“…The deletion of macA results in a significant reduction in the capacity for Fe(III) reduction, suggesting that MacA holds an important role in iron reduction [172]. MacA is a peroxidase which is suggested to transfer electrons to the cytochrome PpcA [163]. Both cytochromes are thought to play a role as periplasmic intermediate electron transfer…”
Section: Abundance Of Eet Related Proteinsmentioning
confidence: 99%
See 2 more Smart Citations